Ensuring Educational Leadership in the Creation and Leadership of Schools - Rudzani Israel Lumadi (Koers : Bulletin for Christian Scholarship, 2017)
Researchers have grappled to speculate about why people in almost all societies share a concern with social justice and equity in education. It is increasingly recognized, internationally and in South Africa, that leading and managing teaching and learning is one of the most important activities for principals and other school leaders. This paper shows that managing teaching and learning are often inadequate, and largely fails to improve educational problems facing school communities. A lot was written about arguably the biggest challenge facing today’s teachers and principals. The question remains how schools could be made to work effectively and equitably for all learners in ever more diverse classrooms. This article will attempt to ensure that there is educational leadership in the creation and management of schools. Quality leadership skills and competencies for effective teaching and learning in schools are also highlighted. The rationale for this study is based on the growing concern that school leadership is not sensitive to the needs of the learners they serve and continue to experience unjustifiable expenditure in relation to community expectations in terms of teaching and learning. The equity theory underpinned this study. It is imperative to note that people feel most comfortable when their relationships are maximally profitable and they are giving and getting exactly what they deserve from their relationships; no more and certainly no less. The ethics of care theory is used as a lens to understand how principals leader and manage schools to improve learner performance. This theory is considered pertinent for this study due to the fact that leaders have authority and power over their subordinates. A leader should possess instructional leadership skills that emphasizes the achievement of the core task, teaching and learning, in schools. Effective leaders understand their staff and learners’ unique needs, can create a supportive environment and engage in practices that build on employee self-confidence to enhance their performance. Ethics of care is deemed suitable for this study since school leaders should have a passion to care for teachers and learners they lead. Ethics of care is a suitable way to connect people and emphasizes helping others. Leaders should go an extra mile to address, nurture and support the needs of the teachers. The role of caring in a school environment has a more specific aim, which is to establish an environment that is conducive to effective teaching and learning because an environment that is caring enhances productivity. An investigation was conducted to explore the effective school leadership through teaching and learning. This effect presents an exhaustive review of the article and suggests a direction for future developments. Based on the study, a qualitative approach was employed to investigate effective school leadership practices as perceived by school leaders. The belief is that schools should be led by quality of leaders in order to produce good results. It is on this backdrop that schools need effective, dedicated, responsible, accountable school leaders, and staff members, if they are to provide quality education for all learners. It became evident from the findings that effective principals put learning at the center of their daily activities and that this can only be achieved if the creation of a conducive environment plays a major role in developing a professional community of teachers who work as a team under an effective instructional leadership. Recommendations evolved from the findings.